(3GdJHUQI aj GdbQGAGJ GdSHYIs - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s
(3ChdgG (B:s
(3Edi JCdjag hfXeg , djchf HGbjkG Ydi eQhQ GdCjGe hGfbQGV GdCfGe, MQUkG efj Ydi HbGA CLQg hLRGA KhGHg s
(3BNQgG (B:s
(3bGd JYGdi (B" (3dGjDNP efce aOjI(B" (3hBNQ GdehLhO efg(B: (3hbO eVi dg fXGFQ cKjQI HCTHY ef gPG GdHjGf s
(3GdfSNI HgG MhGTs
(3GdfSNI oebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B3s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B339s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs